Viscoelastic and Viscoplastic Materials 2016
DOI: 10.5772/64531
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Carbon Nanofiber-Filled Polyamide Composites and Blend of these Composites and TPE

Abstract: For the purpose of developing new engineering materials with sufficient balance among mechanical, electrical, processability, triboloical properties, etc., in this study, we investigated the dynamic viscoelastic properties of carbon nanofiber (CNF) filled polyamide (PA) composites and the blend of these composites and thermoplastic elastomer (TPE) in the molten state, which were mainly obtained in our previous studies. It was found that vapor grown carbon fiber (vapor grown carbon fiber) has a stronger influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…On the contrary, nanocomposites with a hybrid nanofiller system showed the highest melt viscosity value and G 0 for the lowest applied nanoparticle content. This effect was also observed for PA66 with 1% of CNF by Nishitani et al [31] and for PTT-PTMO with 0.1% of E, Young's modulus; σ y , stress at yield; ε y , elongation at yield; σ b , stress at break; ε b , elongation at break. GNP by Paszkiewicz et al [32] It is unclear which mechanism reduces melt viscosity and G 0 value for nanocomposites with a low amount of nanofiller.…”
Section: Sample A)supporting
confidence: 72%
See 2 more Smart Citations
“…On the contrary, nanocomposites with a hybrid nanofiller system showed the highest melt viscosity value and G 0 for the lowest applied nanoparticle content. This effect was also observed for PA66 with 1% of CNF by Nishitani et al [31] and for PTT-PTMO with 0.1% of E, Young's modulus; σ y , stress at yield; ε y , elongation at yield; σ b , stress at break; ε b , elongation at break. GNP by Paszkiewicz et al [32] It is unclear which mechanism reduces melt viscosity and G 0 value for nanocomposites with a low amount of nanofiller.…”
Section: Sample A)supporting
confidence: 72%
“…On the contrary, nanocomposites with a hybrid nanofiller system showed the highest melt viscosity value and G′ for the lowest applied nanoparticle content. This effect was also observed for PA66 with 1% of CNF by Nishitani et al [ 31 ] and for PTT–PTMO with 0.1% of GNP by Paszkiewicz et al [ 32 ] It is unclear which mechanism reduces melt viscosity and G′ value for nanocomposites with a low amount of nanofiller. For CNFs, this could be caused by the self‐lubrication of nanoparticles.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…25 A few authors have reported in the past that the oriented short fibers in the polymer melt lead to reduction of the viscosity during processing. Nishitani and Kitano 26 observed decrease in viscosity of polyamide by addition of 1% of carbon nanofiber at all shear rates. Kopplmayr et al 27 report that pre-orientation of fibers lowers the dynamic viscosity in glass fiber filled PP.…”
Section: Resultsmentioning
confidence: 91%
“…are not known. It is thus very critical to understand the rheological behavior of these biomass composites in the molten state such as processability, internal microstructure, changes and structure-property relationships (8). For this reason, there is a need to investigate its rheological properties.…”
Section: Introductionmentioning
confidence: 99%